2010
DOI: 10.1118/1.3426317
|View full text |Cite
|
Sign up to set email alerts
|

Age‐ and race‐dependence of the fibroglandular breast density analyzed on 3D MRI

Abstract: The results analyzed using the MRI-based method show age- and race-dependence, which is consistent with literature using mammography-based methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 33 publications
2
29
0
1
Order By: Relevance
“…In several previous publications, we analyzed breast density on nonfat-suppressed images. 15,20,[22][23][24][25] The purpose of the present study is to address the current lack of published studies investigating the difference in breast density measured using fat-suppressed versus nonfat-suppressed sequences. Our breast MRI protocol follows the ACR recommendation and uses fat-suppressed sequence for the dynamic contrast enhanced study.…”
Section: Discussionmentioning
confidence: 99%
“…In several previous publications, we analyzed breast density on nonfat-suppressed images. 15,20,[22][23][24][25] The purpose of the present study is to address the current lack of published studies investigating the difference in breast density measured using fat-suppressed versus nonfat-suppressed sequences. Our breast MRI protocol follows the ACR recommendation and uses fat-suppressed sequence for the dynamic contrast enhanced study.…”
Section: Discussionmentioning
confidence: 99%
“…It was revealed that the distribution of breast density in the western women reversed in 40 years old. Another studies reported that Asian women including Chinese women had the highest percent density (Nie et al, 2010;Zulfiqar et al, 2011). Our data revealed that the distribution of breast density in Chinese women reversed in 55 years old.…”
Section: Discussionmentioning
confidence: 99%
“…The research has indicated the relationship between breast density and ethnic differences (Del Carmen et al, 2007). Another studies reported that Asian women including Chinese women had the highest percent density (Nie et al, 2010;Zulfiqar et al, 2011). However, the frequency and age distribution of mammographic breast density patterns Jing Liu et al among Chinese women are not characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Average skin thickness of 1.5mm is used. Fibro-glandular tissue makes up only ~14% of the breast model according to two relatively recent studies [6,7] debunking the 50-50 myth, which states that fibro-glandular tissue makes up 50% of breast. The breast is illuminated by 1 half-wave dipole antenna, 3-element and 5-element halfwave dipole arrays in separate experiments.…”
Section: Model and Simulationmentioning
confidence: 98%